Pervasive Undisclosed Conflicts of Interest in Applied Behavior Analysis Autism Literature - Bottema-Beutel, Kristen; Crowley, Shannon (Frontiers in Psychology, 2021)
Abstract Many autistic people (including researchers and non-researchers) are becoming increasingly involved in, and increasingly critical of, autism intervention research. They have expressed concerns regarding applied behavior analysis (ABA) interventions on a number of grounds, one of which is the prevalence of conflicts of interest (COIs) among autism intervention researchers. These concerns are now also being addressed by non-autistic researchers. COIs can introduce bias into the research process, and allow researchers to demonstrate positive effects for interventions that are not actually effective. Despite these concerns, there are no studies to date that examine the prevalence of COIs in behavioral journals. Because ABA services are routinely provided to autistic people in the United States as a means to address difficulties experienced by autistic people, this is an important area of investigation. We tallied author COIs in articles published over a one-year period that tested, commented on, or reviewed ABA autism intervention strategies, extracted from eight journals devoted to publishing behavioral research. We coded included studies for COIs related to researcher employment as an ABA clinical provider or a training consultant to ABA clinical providers. We found that 84% of studies had at least one author with this type of COI, but they were only disclosed as COIs in 2% of studies. Additionally, 87% of studies with statements claiming the authors did not have COIs, were authored by researchers found to have clinical/training consultancy COIs. Pervasive, undisclosed COIs likely lead to researcher bias, and could at least partially account for persistent poor quality research in this area. The high prevalence of COIs among this research corroborates the concerns expressed by many autistic people. The autism community-- including autistic people, autism researchers, and other stakeholders-- should be aware of the prevalence of undisclosed COIs in this literature and take this into account when using, providing, or recommending ABA services.